The Ethics of Decoration in Architecture (Journal of University of Babylon for Engineering Sciences, 2018)
The decoration has been associated with various human achievements since ancient times and has been considered by some of theses  as an additional, non-mandatory , can be probability  remove , subtract and dispensable. It is misunderstood as a mere addition and an instrument  for beauty as its artistic characteristics, especially the decorative  jewelry. In contrast to the concept of mandatory  ethics concept  which associated withboth for purposes and values aspects, that contrast highlighted the need to discuss them together to investigate the ethical aspects of decorating in architectural output to undermine those ideas, which considered decorating as a surplus only.The research problem was explained by "absence  a clear conception of the ethical indicators of decorating the product of architecture", Thus the goal of the research is that "put the ethical indicators of decoration the architectural output at the level of plans and facades" , so the research put hypothesis as "highlighting the ethics of decoration within both the subcontractor and the apparent levels In each of plans and facades, to achieve architectural output as a whole", it focused on uncovering the ethical indicators of decoration the architectural output, in order to present a special theoretical framework for the indicators of moral decoration at the level of plans and the facades together,It has been confirmed that the decoration at the level of the plans and the facade both, that confirmed its commitment to the functional aspects economic , safety environmental construction, as well as to the aesthetic aspects of expressive and symbolic especially Tectonics, as determined the apperance of architectural output as a whole Today, after its development into digital tectonics for the production of digital surfaces, which were described as skins to overlap the structure (the structure - the skin) and their material together weaving decoration process thanks to the digital potentials to represent the digital surface space or metaphysical fabric and a living space for various functional and aesthetic values in the current era, including richer functional plans and expression facades.